Explaining variation in the implementation of global norms: Gender mainstreaming of security in the OSCE and the EU - Jenichen, Anne; Joachim, Jutta; Schneiker, Andrea (International Political Science Review)
Why do regional security organizations choose different approaches to implementing global gender norms? To address this question, we examine how the Organization for Security and Co-operation in Europe (OSCE) and the European Union (EU) integrated requirements derived from UN Security Council Resolution 1325 (UNSCR 1325) on women, peace and security into their security policies. We identify differences in scope and dynamics between the change processes in the two organizations. The OSCE simply adapted its existing gender policy and has not changed it since, whereas the EU introduced a new, more extensive and specific policy, which it has already amended several times. Drawing on historical institutionalism and feminist institutionalism, we found that, first, reform coalitions prepared the ground for gender mainstreaming in the organizations$1 (Brespective security policies; and that, second, embedded policy structures, including rules and norms about external interaction as well as existing policy legacies, were responsible for the different approaches of the EU and OSCE with respect to UNSCR 1325. - Reproduced.s
Keywords: Peace; Security; European Union